2014
DOI: 10.1186/1472-6882-14-374
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicines (CAMs) among type 2 diabetes patients in Sri Lanka: a cross sectional survey

Abstract: BackgroundThe incidence of chronic illnesses has increased worldwide. Diabetes is one such illness and 80% of the diabetic population lives in the developing world. There is a rapidly growing trend towards the use of Complementary and Alternative Medical practices in Diabetes. Sri Lanka is a developing Asian nation with a rich culture of Ayurvedic and native medical culture.The objective of this study was to find the prevalence of use of CAMs in a diabetic population attending a large multiethnic diabetes faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 16 publications
2
47
0
Order By: Relevance
“…A similar rate was shown by another study at a health clinic in Sepang (Ching et al 2013a). In Sri Lanka, Medagama et al (2014) found 62.8% of patients with diabetes mellitus used bitter gourd as supplements with the intention to help controlling the blood glucose level. A study on two local types of bitter gourd (peria katak and peria kambas) in Malaysia found that they both had hypoglycaemic effects through inhibition of αα-amylase and αα-glucosidase activities (Ee Shian et al 2015).…”
Section: Discussionsupporting
confidence: 61%
“…A similar rate was shown by another study at a health clinic in Sepang (Ching et al 2013a). In Sri Lanka, Medagama et al (2014) found 62.8% of patients with diabetes mellitus used bitter gourd as supplements with the intention to help controlling the blood glucose level. A study on two local types of bitter gourd (peria katak and peria kambas) in Malaysia found that they both had hypoglycaemic effects through inhibition of αα-amylase and αα-glucosidase activities (Ee Shian et al 2015).…”
Section: Discussionsupporting
confidence: 61%
“…The levels of biochemical parameters were significantly lower in the T2D patients who practiced CAM when compared to non-CAM users which is in agreement with the earlier studies [24]. Previous studies have shown that blood glucose level could be maintained by improving muscle glucose uptake and by enhancing insulin action on blood glucose [25][26][27].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were obtained in a study which was conducted by Medagama AB, in Srilanka and Singh et al, in India. 19,20 This might be possibly due to the interplay of various factors like drug-herb interaction, drug-food interactions among ayurvedic and naturopathy users respectively. However, those who practiced yoga reported a better sense of well-being and fewer episodes of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%